MEMS vibratory gyroscopes: structural approaches to improve robustness - Acar, Cenk (Springer, 2017)
MEMS Vibratory Gyroscopes provides a solid foundation in the theory and fundamental operational principles of micromachined vibratory rate gyroscopes, and introduces structural designs that provide inherent robustness against structural and environmental variations. In part one, the dynamics of the vibratory gyroscope sensing element is developed, common micro-fabrication processes and methods commonly used in inertial sensor production are summarized, design of mechanical structures for both linear and torsional gyroscopes are presented, and electrical actuation and detection methods are discussed along with details on experimental characterization of MEMS gyroscopes. In part two, design concepts that improve robustness of the micromachined sensing element are introduced, supported by constructive computational examples and experimental results illustrating the material.